Peningkatan Sifat Mekanis Pada Permukaan Poros Roda Hand Tractor Lokal Dengan Flame Hardening - Santoso, Teguh; , Patna Partono, ST, MT (2017)
Agricultural technology hand tractor in Indonesia today still use foreign-made, one spare part of a hand tractor is wheel axle. Until recently axle replacement of hand tractors still have to use products made by manufacturers from other countries, not local manufacturers, so the cost is expensive and takes a long time to procure. Therefore, the local industry should be able to make its own axle in order to overcome these shortcomings, the price obtained axle cheaper and faster availability. However, local producers should be able to make a product that is the result axle-quality foreign products. Furthermore, the purpose of this research is how to create and improve the mechanical properties of the axle to hand tractor. Improved mechanical properties on the wheel axle carried by the surface hardening using flame hardening, ie by heating with a flame from a welding tool brander on the surface of the steel S15CK to a temperature austenitic 850 ° C for 5 minutes, then immediately processed quenching on the surface of the shaft with method of spraying with water media. Products from the surface hardening process of testing the chemical composition with ASTM E350-12, Vickers hardness with ASTM E384 and ASTM standards microstructure with E3. Results of hardness testing showed the value of hardness at the surface of S15CK steel shaft of 710.16 HV and in the middle (center) of S15CK steel shaft of 482,04 HV. While the value of S15CK steel axle violence before being processed surface hardening is at 200.03 HV. While the hand tractor axle material produced abroad hardness value obtained on the surface of the shaft is equal to 624 HV and in the middle (center) of the shaft is equal to 284 HV. In the steel shaft surface hardness value (mechanical properties) are much higher than those in the middle (center), due to the surface hardening process by the method of flame hardening.